Banks as Multioutput Oligopolies: An Empirical Evaluation of the Retail and Corporate Banking Markets - Sigbjørn Atle Berg; Moshe Kim (Norges Bank, 1994)
The distinction between retail and corporate banking markets is of much importance in real life banking organizations. The two markets differ with respect to concentration, the importance of informational asymmetries, and the extent of customer mobility. Within a standard conjectural variation model we empirically characterize the strategic behaviour within each of these markets, and also focus on cross market interactions to see whether initial moves in one market affects the equilibrium in the other market.
hdl:11250/2500581
Keywords: 330; banking; multioutput production; conjectural variation